CORRELATION BETWEEN BLOOD METABOLITE AND REPRODUCTIVE PERFORMANCE OF LACTATING HOLSTEIN FRIESIAN CROSSBRED COWS IN SMALLHOLDER FARMERS - Diah Tri Widayati; Marcella Arka Paramita; Elisa Dwiviyanti; Yustina Yuni Suranindyah (Universitas Syiah Kuala, 2019)
This study examined the correlation between the concentration of blood metabolites (triglyceride, albumin, phosphorous) on the reproductive performances (S/C and PPM) of lactating Holstein Friesian crossbred (HFC) cows. Blood samples were collected through the caudal vein 8 hours after feeding and the plasma was analyzed at the Integrated Research and Testing Laboratory of Universitas Gadjah Mada (LPPT UGM). Samples were stored at 5° C. Triglyceride, albumin, and phosphorous were measured using glucose oxidase-phenol 4-aminoantipyrine (GOD-PAP) method, photometric bromocresol green method, and cypress diagnostic, respectively. Blood metabolites data were analyzed using Pearson correlation model. The results showed that the correlation coefficients of triglycerides, albumin, and phosphorus levels on PPM and S/C were -0.521 and -0.650; -0.447 and -0.612; -0.513 and -0.700, respectively. In conclusion, there are significant negative correlation between triglyceride, albumin and phosphorus levels on the PPM, and very significant negative correlation between triglyceride, albumin and phosphorus levels on the S/C of lactating HFC cows.